Asymmetric impact of climate change on banking system stability in selected sub-Saharan economies - Amo-Bediako, Emmanuel; Takawira, Oliver; Choga, Ireen; Otchere, Isaac; Siaw-Asamoah, Dorothy (The Economics and Finance Letters, 2024)
This study is an empirical examination of the asymmetric impact of climate change on banking system stability in selected sub-Saharan economies. The study leverages a quantitative research approach through a panel non-linear ARDL framework and data from 29 selected economies, which spans 1996-2017. Findings from the study reveal that in the long term, partial sums of temperature have an insignificant relationship with banking system stability. Further, partial sums of precipitation are negatively related to banking system stability in the long term. The finding indicates that both positive and negative precipitation do harm banking system stability in the selected sub-Saharan economies. Moreover, we find that partial sums of greenhouse gas emissions had an insignificant relationship with banking system stability. In addition, we conclude that greenhouse gases (positive and negative) do not impair banking system stability in selected sub-Saharan economies in the long term. We surmise from the findings that both positive and negative climate change indexes are harmful to banking system stability. On the short-term asymmetric impact, we discover that partial sums of temperature, precipitation, and climate change index do not harm banking system stability. However, negative greenhouse gas emissions are pernicious to the banking system’s stability in the short term. Conversely, positive greenhouse gas levels were statistically insignificant. The study recommends that central banks and monetary authorities in Sub-Saharan Africa design green banking policies to push the climate change agenda in the banking sector.